Estimation of the subsidence around the trace of the San Ramón Chile fault, using the SBAS DInSAR technique through TerraSAR-X images - Patricio Lamperein-Polo; Paulina Vidal-Páez; Waldo Pérez-Martínez (Revista de Teledetección)
Chile is one of the countries with the highest seismicity in the world and is affected by three types of seismogenic sources; interplate, intraplate and superficial or cortical intraplate. In this context, in the eastern sector of the city of Santiago, capital of Chile, the Falla San Ramón (FSR) is located. It is a cortical seismogenic source, which threatens its habitants and the various economic activities that are located in that sector, geological hazards such as earthquakes and mass removals. In relation to the above, this study aims to identify and establish the subsidence areas in a longitudinal strip of the Santiago mountain front and its impact on the neighboring communes to the FSR trace during the years 2011 to 2017. To do this, The DInSAR technique was used with the Small Baseline Subset (SBAS) algorithm through a time series of images from the TerraSAR-X (TSX) satellite. The results show subsidence zones, with average displacements ranging from -13.11 mm to +9.89 mm, with an average annual speed rate of -2.19 to +1.65 mm/year.